2023
DOI: 10.3389/fpubh.2022.980958
|View full text |Cite
|
Sign up to set email alerts
|

Getting to implementation: Adaptation of an implementation playbook

Abstract: IntroductionImplementation strategies supporting the translation of evidence into practice need to be tailored and adapted for maximum effectiveness, yet the field of adapting implementation strategies remains nascent. We aimed to adapt “Getting To Outcomes”® (GTO), a 10-step implementation playbook designed to help community-based organizations plan and evaluate behavioral health programs, into “Getting To Implementation” (GTI) to support the selection, tailoring, and use of implementation strategies in healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…For example, in several cases an adaptation could be characterized as a context change to both the format and personnel. Two previous studies described similar experiences when using the FRAME-IS to document adaptations to multifaceted implementation strategies supporting integration of practice-based interventions [13,14]. For example, Mangale et al [13] found that adaptations to the implementation strategies were not mutually exclusive and fit within several categories resulting in 'unavoidable overlap.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, in several cases an adaptation could be characterized as a context change to both the format and personnel. Two previous studies described similar experiences when using the FRAME-IS to document adaptations to multifaceted implementation strategies supporting integration of practice-based interventions [13,14]. For example, Mangale et al [13] found that adaptations to the implementation strategies were not mutually exclusive and fit within several categories resulting in 'unavoidable overlap.…”
Section: Discussionmentioning
confidence: 95%
“…A small but growing number of studies have utilized the FRAME-IS to provide important information on the adaptability of various implementation strategies in diverse settings including FQHCs [6,[13][14][15][16]. However, most of these studies are limited by their focus on a discrete implementation strategy (e.g., training), which do not reflect the complexity of multifaceted strategies such as practice facilitation (PF).…”
Section: Introductionmentioning
confidence: 99%
“…Two previous studies described similar experiences when using the FRAME-IS to document adaptations to multifaceted implementation strategies supporting integration of practice-based interventions. ( 13 , 14 ) For example, Mangale et al( 13 ) found that adaptations to the implementation strategies were not mutually exclusive and fit within several categories resulting in ‘unavoidable overlap.’ Haley et al ( 9 ) also described challenges to tracking adaptations to a multifaceted implementation strategy using existing frameworks. Like our approach, the authors addressed these challenges by adding more detailed information on the changes using the ERIC taxonomy and developed new codes to augment the broad categorization of strategies offered by current frameworks.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies described similar experiences when using the FRAME-IS to document adaptations to multifaceted implementation strategies supporting integration of practicebased interventions. (13,14) For example, Mangale et al (13) found that adaptations to the implementation strategies were not mutually exclusive and t within several categories resulting in 'unavoidable overlap.' Haley et al ( 9) also described challenges to tracking adaptations to a multifaceted implementation strategy using existing frameworks.…”
Section: Discussionmentioning
confidence: 99%